Catching fire - Collins, Suzanne (New York : Scholastic Press, 2009)
By winning the annual Hunger Games, District 12 tributes Katniss Everdeen and Peeta Mellark have secured a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion.
Accelerated Reader/Renaissance Learning
A Junior Library Guild selection.
Notable Social Studies Trade Books for Young People, 2010.
Keywords: Insurgency -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Contests -- Juvenile fiction; Dystopias -- Juvenile fiction; Insurgency -- Fiction; Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction; Young adult fiction